Education Equity and Inclusive Capacity Building in Greening Global Value Chains: A Framework for Sustainable Development and Social Inclusion - Viraj P. Tathavadekar; Nitin R. Mahankale (Journal of Cross-Disciplinary Sustainability Innovations, 2026)
Global value chains are rapidly moving toward sustainability, offering potential opportunities for market development, but the flipside presents challenges concerning equity and inclusive participation in learning processes. This paper proposes a comprehensive framework for designing inclusive capacity-building programs that utilize digital learning technologies, community-based training models, and policy instruments to democratize access to green value chain opportunities. The framework synthesizes ideas including multi-stakeholder partnerships, competency-based learning pathways, and community-centered approaches to overcome systemic barriers encountered by marginalized communities. Through the review of best-case studies and an analysis of existing gaps in education, this research sets the foundation upon which scalable solutions toward environmental sustainability and social equity could be pursued. It further shows that the integration of digital infrastructure, policy support, and cultural responsiveness in a framework can provide viable pathways for meaningful engagement of underrepresented populations in emerging green economies. The results of this implementation process indicate increased economic opportunities, greater community resilience, and uplifted organizational capacity for innovation, which advances more equitable and sustainable patterns of development.